Short environmental enrichment in adulthood rescues the neurons of anterior bed nucleus of stria terminalis from effects of early life stress - Goh, Vivian Ching Xian (2016)
Early-life stress (ELS) has been known to increase ones susceptibility to neuropsychological disorders in adulthood. The relationship between ELS and its manifestation in adulthood has spurred many studies to explore their association. The bed nucleus of stria terminalis (BNST) is central for manifestation of anxiety and is a crucial messenger to the Hypothalamus-Pituitary-Adrenal (HPA) axis. Therefore, the development of psychopathologies could possibly be due to a dysfunctional BNST. Even so, the availability of studies on how ELS affects the dendritic tree of BNST is minimal. Thus, this studyaims to investigate how ELS,in the form of maternal separation (MS), affects the morphologies and spines of BNST neurons in adult male rats, and if environmental enrichment could reverse the damage brought upon by MS. We report significant atrophy in the total dendritic length and number of branch points as well as increased spines in BNST neurons as a result of MS. We have also ruminated that different regions of BNST is involved in mediating different forms of stress responses which explains for the dissimilar BNST plasticity observed here. Therefore, this study hopes to provide an additional insight that adds to the immense knowledge that accounts for resilience towards ELS.